An enhanced scheme for QoS in mobile IPv6 environment - Hussien, Loay F.; Hassan Abdalla Hashim, Aisha; Anwar, Farhat; Khalifa, Othman Omran; Hameed, Shihab A. (2011)
The need for Quality of Service (QoS) capabilities in the Internet originates from the fact that Best-Effort service and datagram routing do not meet up the desires of many new applications. Video conferencing, voice over IP (VoIP), and video on demand (VoD) are examples of real-time applications. These applications require some degree of resource assurance in order to operate effectively. Vast and diverse user requirements create the need for service providers to offer different levels of services in the Internet. Therefore, the Internet community has developed a number of new technologies to address these issues. Differentiated Service (DiffServ) is one of them that has endorsed by Internet Engineering Task Force (IETF) as a scalable solution to satisfy the requirements of new application. In fact, it is anticipated that more mobile users will be connected to the Internet rather than PCs users. The mobile users are interesting to get similar QoS in mobile terminals as in fixed terminals (wired networks) in order to run real-time applications. MIPv6 protocol doesn't provide QoS guarantees to its users same as traditional Internet IP. This poses a problem to real-time applications that required QoS guarantees. Thus merging mobility with QoS is still ongoing research by the networking researchers. To achieve seamless handover and delivery of realtime traffic in mobile environment, DiffServ model is deployed in MIPv6 network. This paper presents an overview of integrating DiffServ in mobile environment. It also proposes a new scheme (DiffServ-MIPv6) to fulfill the needs of both QoS guaranteed and mobility in communication. The proposed scheme intends to reduce handover latency for the mobile node as well as alleviates packet losses.